German Social Cultural Society in Zielona Góra = Towarzystwo Społeczno-Kulturalne Mniejszości Niemieckiej w Zielonej Górze - Kruk, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article covers the activity of the German minority in area around Zielona Gora from the 1990s until today. The activity of the German Social Cultural Society in Zielona Gora has been presented. The author emphasized the wide range of activities of the Society, e.g. the educational actions, which promote the Lubusz Voivodeship as well as its cooperation with other institutions. The cultural activity of the German minority has been described, e.g. based on the magazine "Grunsberger Monatsblatt".
Keywords: mniejszość niemiecka; województwo lubuskie; Zielona Góra; German minority; Lubuskie voivodship